Moral judgments in social dilemmas: How bad is free riding? - Robin P. Cubitt; Michalis Drouvelis; Simon Gaechter; Ruslan Kabalin (Center for Economic Studies and ifo Institute (CESifo), 2010)
In the last thirty years, economists and other social scientists have investigated people's normative views on distributive justice. Here we study people's normative views in social dilemmas, which underlie many situations of economic and social significance. Using insights from moral philosophy and psychology we provide an analysis of the morality of free riding. We use experimental survey methods to investigate people's moral judgments empirically. We vary others' contributions, the framing ('give-some' vs. 'take-some') and whether contributions are simultaneous or sequential. We find that moral judgments of a free rider depend strongly on others' behaviour; and that failing to give is condemned more strongly than withdrawing all support.
Keywords: C90; D63; H41; 330; moral judgments; moral psychology; framing effects; public goods experiments; free riding; Soziale Gerechtigkeit; Verteilungsgerechtigkeit; Ethik; Trittbrettfahrerverhalten; Öffentliches Gut; Test; Großbritannien